Radiofrequency ablation or microwave ablation combined with transcatheter arterial chemoembolization in treatment of hepatocellular carcinoma by comparing with radiofrequency ablation alone - Yi, Yongxiang; Zhang, Yufeng; Wei, Qiang; Zhao, Liang; Han, Jianbo; Song, Yan; Ding, Ying; Lu, Guilan; Liu, Junmao; Ding, Huaiying; Dai, Feng; Tang, Xiaojun (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To compare radiofrequency ablation (RFA) or microwave ablation (MWA) and transcatheter arterial chemoembolization (TACE) with RFA or MWA monotherapy in hepatocellular carcinoma (HCC). Methods: A prospective, randomized, controlled trial was conducted on 94 patients with HCC ≤7 cm at a single tertiary referral center from June 2008 to June 2010 at the Department of Hepatobiliary Surgery, the Second Affiliated Hospital of Southeast University. The patients were randomly assigned into the TACE-RFA or TACE-MWA (combined treatment group) and the RFA-alone or MWA-alone groups (control group). The primary end point was overall survival. The secondary end point was recurrence-free survival, and the tertiary end point was adverse effects. Results: Until the time of censor, 17 patients in the TACE-RFA or TACE-MWA group had died. The median follow-up time of the patients who were still alive for the TACE-RFA or TACE-MWA group was 47.5±11.3 months (range, 29 to 62 months). The 1-, 3- and 5-year overall survival for the TACE-RFA or TACE-MWA group was 93.6%, 68.1% and 61.7%, respectively. Twenty-five patients in the RFA or MWA group had died. The median follow-up time of the patients who were still alive for the RFA or MWA group was 47.0±12.9 months (range, 28 to 62 months). The 1-, 3- and 5-year overall survival for the RFA or MWA group was 85.1%, 59.6% and 44.7%, respectively. The patients in the TACE-RFA or TACE-MWA group had better overall survival than the RFA or MWA group [hazard ratio (HR), 0.526; 95% confidence interval (95% CI), 0.334-0.823; P=0.002], and showed better recurrence-free survival than the RFA or MWA group (HR, 0.582; 95% CI, 0.368-0.895; P=0.008). Conclusions: RFA or MWA combined with TACE in the treatment of HCC ≤7 cm was superior to RFA or MWA alone in improving survival by reducing arterial and portal blood flow due to TACE with iodized oil before RFA.